Предмет: Алгебра,
автор: Адия1111
номер 586 помогите пожалуйста,срочно нужно!
Приложения:
Ответы
Автор ответа:
0
y/(3-y)+[(y²+3y)/(2y+3)]·[(3+y)/(y²-3y)-y/(y²-9y)]=
=y/(3-y)+[y(y+3)/(2y+3)]·{[(3+y)(3+y)-y²]/[y(y-3)(y+3)]}=
=y/(3-y)+[1/(2y+3)]·{[(9+6y+y²)-y²]/[(y-3)]}=
=y/(3-y)+[1/(2y+3)]·{[(3(3+2y)]/[(y-3)]}=y/(3-y)+[1]·{[(3)]/[(y-3)]}=
=(y-3)/(3-y) =-1 не зависит от y/
=y/(3-y)+[y(y+3)/(2y+3)]·{[(3+y)(3+y)-y²]/[y(y-3)(y+3)]}=
=y/(3-y)+[1/(2y+3)]·{[(9+6y+y²)-y²]/[(y-3)]}=
=y/(3-y)+[1/(2y+3)]·{[(3(3+2y)]/[(y-3)]}=y/(3-y)+[1]·{[(3)]/[(y-3)]}=
=(y-3)/(3-y) =-1 не зависит от y/
Похожие вопросы
Предмет: Информатика,
автор: vovareut2008
Предмет: Биология,
автор: kathringolubeva
Предмет: Геометрия,
автор: angelinkamandarinka9
Предмет: Математика,
автор: Алишка878787
Предмет: Математика,
автор: sayaraur87